On Rereading Harry J. Carman's Social and Economic History of the United States - Goodrich, Carter (Journal of Economic Literature, 1969)
V OLUME ONE is dedicated to 'Four Generations of Students in Columbia College, and nonappearance of a proposed third volume was perhaps due to Harry Carman's added duties after he became, in preconfrontation days, very popular Dean of College. The reappearance of his History is a welcome event and offers an occasion to reflect on changes since its publication in American economic history. Even in their day these volumes did not purport to be economic history in strict sense. The title reads 'Social and Economic, and addition of Intellectualr would have been entirely appropriate. There was already a substantial corpus of professional work in American economic history. Guy Stevens Callender's Selections from Economic History of United States, 1765-1860, with its still unsurpassed analytical introductions, had appeared as early as 1909. The first edition of Harold Underwood Faulkner's American Economic History was published in 1924 and its second in 1931. Edward C. Kirkland's admirably written History of American Economic Life came out first in 1932. Of major texts written by economists, Ernest L. Bogart's Economic History of United States, with its particularly clear analyses of trade relationships, appeared in 1930. Although Chester W. Wright did not bring out his text until 1941, most of its material, including a wealth of statistical tables and his analyses of standard of living at various periods, was available to his students at Chicago as early as 1920. These books, indeed, and numerous monographs cited at ends of Carman's chapters, show how much of factual knowledge of American economic development, if not its theoretical analysis, was already at hand in early 1930s. With this background Carman book describes various sectors of economic activity with a full knowledge of techniques and processes, with a wealth of human detail drawn from contemporary sources, and with a firm grasp of geographic and economic determinants of regional specialization. The chapter on The Colonial Farmer is particularly brilliant. Much of work is devoted to play of economic forces in political life. Two chapters are given to American Revolution and a third to making of Constitution. Mercantilist restrictions are regarded as foremost among causes of Revolution, and in both these struggles, Carman follows Beard in discerning a sharp cleavage between propertied-business men and common people. Similarly, two chapters are devoted to Civil War and the sectional rivalry leading to that * Harry J. Carman. Social and Economic History of United States, volume I, From Handicraft to Factory, 1500-1820; volume II, The Rise of Industrialism, 1820-1875. New York: D. C. Heath & Co., 1930, 1934. Reprinted New York: Johnson Reprint Corporation, 1968. Pp. xii + 616; x + 684, 2 vols. $47.50.